Audit quality and accrual quality: Evidence from Saudi -listed firms - Alduraywish, Yaqoub (Asian Economic and Financial Review, 2024)
This research explores the association between audit quality and accrual quality. Drawing upon the self-interest perspective, previous theories on ownership and management contend that when shareholders are excluded from managerial responsibilities, it grants greater power to management, leading to potential benefits for themselves rather than prioritizing the interests of the business ownership, thereby influencing the firm's performance. The literature preceding this study suggests that auditors play a significant role in mitigating conflicts of interest between management and shareholders. By providing assurance engagement services, auditors positively impact the firm's accruals. This paper posits the hypothesis that clients benefiting from higher audit quality experience fewer agency problems, resulting in improved accrual quality for the firm. To test this hypothesis, the study collects data from the financial reports of non-financial Saudi firms listed on the Saudi Stock Exchange for the fiscal years spanning from 2015 to 2019. The paper employs various regression models, including random effect (RE) and Probit models, to assess accrual quality. Consistent with the expected outcomes, this paper reveals that firms audited by the Big four exhibit an accruals ratio of approximately 27.9% compared to firms audited by non-Big Four auditors. This paper contributes to the body of knowledge by showing the role of audit in the Middle East context in increasing firm’s accruals, and investors can use the findings of this paper in their investment decisions.